Overall survival with palbociclib plus endocrine therapy versus capecitabine in postmenopausal patients with hormone receptor-positive, HER2-negative metastatic breast cancer in the PEARL study. (June 2022) - Martín, Miguel; Zielinski, Christoph; Ruiz-Borrego, Manuel; Carrasco, Eva; Ciruelos, Eva M.; Muñoz, Montserrat; Bermejo, Begoña; Margelí, Mireia; Csöszi, Tibor; Antón, Antonio; Turner, Nicholas; Casas, María I.; et al.
Abstract: Background: An earlier analysis of the PEARL phase III study showed that palbociclib plus endocrine therapy (ET) does not improve progression-free survival (PFS) over capecitabine in aromatase inhibitor-resistant, hormone receptor-positive/human epidermal growth factor receptor 2-negative metastatic breast cancer (MBC) patients. Here, we report the final overall survival (OS) analysis. Methods: Postmenopausal patients (N = 601) were randomized 1:1 to capecitabine or palbociclib plus ET (exemestane, Cohort 1; fulvestrant, Cohort 2). OS was analysed in Cohort 2, the wild-type ESR1 population and the overall population. Additionally, we analysed subsequent systemic therapies and explored PFS2 (time from randomization to the end of the first subsequent therapy/death). Results: OS was 31.1 months for palbociclib plus fulvestrant and 32.8 months for capecitabine (adjusted hazard ratio [aHR] 1.10, 95% confidence interval [CI] 0.81–1.50, P = 0.550). In the wild-type ESR1 population, OS was 37.2 months for palbociclib plus ET and 34.8 months for capecitabine (aHR 1.06, 95% CI 0.81–1.37, P = 0.683). In OS analyses, no subgroup showed superiority for palbociclib plus ET over capecitabine. OS in the overall population was 32.6 months for palbociclib plus ET and 30.9 months for capecitabine (P = 0.995). Subsequent systemic therapy was given to 79.8% and 82.9% of patients with palbociclib plus ET and capecitabine, respectively. Median PFS2 was similar between study arms (Cohort 2, P = 0.941; wild-type ESR1 population, P = 0.827). No new safety findings were observed. Conclusions: Palbociclib plus ET did not show a statistically superior OS compared to capecitabine in MBC patients progressing on aromatase inhibitors. Trial registration: NCT02028507 (ClinTrials.gov), 2013-003170-27 (EudraCT). Highlights: Overall survival (OS) was assessed in patients with metastatic breast cancer (MBC). OS was similar for palbociclib + fulvestrant and capecitabine in AI-resistant MBC. The results were independent of the ESR1 mutational status. In wild-type ESR1 tumours, palbociclib + ET and capecitabine also had similar OS. Progression-free survival 2 was similar in both treatment arms.